2021
DOI: 10.1002/jsfa.11141
|View full text |Cite
|
Sign up to set email alerts
|

Primary research on sampling scheme for analyzing mycotoxin distribution in wheat and rice fields

Abstract: BACKGROUND Mycotoxins are among the most severe food contaminants. Deoxynivalenol and aflatoxin contamination are predominant in wheat and rice, respectively. Nowadays, there are no standardized and approved grain‐sampling schemes worldwide. This study aimed to develop a scientific grain‐sampling scheme to investigate the regularity of mycotoxin distributed in wheat and rice fields. The data were analyzed with analysis of variance and cluster analysis to select a better sampling scheme. RESULTS Considering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Research on sampling and sample processing published over the past year include characterisation of mycotoxin distributions among maize kernels (Chavez et al, 2022) and within fields (Yi et al, 2021), an enhanced analysis of existing data sets on mycotoxin spatial distribution in bulk volumes (Kerry et al, 2021), and descriptions of sampling techniques for blood (Vidal et al, 2021), grain dust (Limay-Rios and Schaafsma, 2021), and for pooling samples for mycotoxin screening (Cheng et al, 2020). A very welcome retrospective analysis was also published on the disappointing decrease in researchers' consideration of proper sampling and processing of maize (Kumphanda et al, 2021).…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on sampling and sample processing published over the past year include characterisation of mycotoxin distributions among maize kernels (Chavez et al, 2022) and within fields (Yi et al, 2021), an enhanced analysis of existing data sets on mycotoxin spatial distribution in bulk volumes (Kerry et al, 2021), and descriptions of sampling techniques for blood (Vidal et al, 2021), grain dust (Limay-Rios and Schaafsma, 2021), and for pooling samples for mycotoxin screening (Cheng et al, 2020). A very welcome retrospective analysis was also published on the disappointing decrease in researchers' consideration of proper sampling and processing of maize (Kumphanda et al, 2021).…”
Section: Samplingmentioning
confidence: 99%
“…The lack of apparent bias is most likely reflecting very high kernelto-kernel differences, that overshadowed any effect from kernel selection bias. Yi et al (2021) sampled two fields of wheat and rice and performed a spatial analysis of deoxynivalenol (DON) and aflatoxins, respectively. The fields were segmented into three sections (middle, peripheral, and 'other' -the span between the middle and the periphery of the fields).…”
Section: Samplingmentioning
confidence: 99%
“…21 The samples were processed and detected for mycotoxin using an enzyme-linked immunosorbent assay kit (Jiangsu SUWEI Microbiology Research Co. Ltd, China, Wuxi.). 12 Each sample selection was performed in triplicate.…”
Section: Moisture and Mycotoxin Testing Of Wheat Samplesmentioning
confidence: 99%
“…Rational sample selection is the first step to detecting mycotoxin content in grains and food. Scientific and reasonable selection of samples can accurately reflect the contamination degree of food and its products 12 . However, few studies have been reported considering how to sample grains from a granary and precisely detect mycotoxin in the samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation